Arctic charr and brown trout data from a compensatory nutrient enrichment experiment in an oligotrophicated hydropower reservoir - Vrede, Tobias; Milbrink, Göran; Rydin, Emil (Swedish University of Agricultural Sciences, 2025)
This is a data set with length (fork lengt, mm), wet weight (g), condition (g/cm3x100) and age (+years) of Arctic charr (Salvelinus alpinus) and brown trout (Salmo trutta) from a whole lake experiment in two hydropower reservoirs in Jämtland region, Sweden. Nutrients (phosphorus and nitrogen) were added to Stor-Mjölkvattnet and upstream Burvattnet was a reference system. The study cover the years 2001-2009 and 2016, and nutrients were added to Stor-Mjölkvattnet during 8 consecutive years (2002-2009). For detailed method description, see Milbrink et al. (2025), https://doi.org/10.1080/02705060.2025.2511868

Detta är ett dataset med längd (standardlängd, mm), våtvikt (g), kondition (g/cm3x100) och ålder (+år) hos röding (Salvelinus alpinus) och öring (Salmo trutta) från ett helsjöförsök i två vattenkraftsmagasin i Jämtland. Näring (fosfor och kväve) tillsattes i Stor-Mjölkvattnet och uppströms liggande Burvattnet var referenssystem. Studien omfattar åren 2001-2009 och 2016, och näringsämnen tillfördes Stor-Mjölkvattnet under 8 på varandra följande år (2002-2009). En detaljerad metodbeskrivning finns i Milbrink et al. (2025), https://doi.org/10.1080/02705060.2025.2511868
Röding- och öringdata från ett helsjöexperiment med kompensatorisk näringstillsats i ett oligotrofierat vattenkraftsmagasin
Keywords: LAKES/RESERVOIRS; fishes; fisk; Salvelinus alpinus; röding; Salmo trutta; öring; hydropower; vattenkraft; oligotrophication; oligotrofiering; whole lake experiment; helsjöexperiment; Environmental Sciences; Miljövetenskap; Ecology; Ekologi; Fish and Wildlife Management; Vilt- och fiskeförvaltning